2016
DOI: 10.1038/ncomms11425
|View full text |Cite
|
Sign up to set email alerts
|

Ultraflexible organic amplifier with biocompatible gel electrodes

Abstract: In vivo electronic monitoring systems are promising technology to obtain biosignals with high spatiotemporal resolution and sensitivity. Here we demonstrate the fabrication of a biocompatible highly conductive gel composite comprising multi-walled carbon nanotube-dispersed sheet with an aqueous hydrogel. This gel composite exhibits admittance of 100 mS cm−2 and maintains high admittance even in a low-frequency range. On implantation into a living hypodermal tissue for 4 weeks, it showed a small foreign-body re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
194
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 33 publications
(43 reference statements)
2
194
0
Order By: Relevance
“…The electrodes were aligned to edges of the microchambers manually to keep their distance almost the same around the microchamber for uniform electrical stimulation of individual spheroids. Hybrids of hydrogel and organic electrodes are useful for biocompatible electronic systems and many types have been reported, however, the composite of PVA hydrogel and PEDOT‐coated CF (CF‐PEDOT) electrodes is reported for the first time as far as we know. The cover made of PVA hydrogel was tightly sealed to the body with pins.…”
Section: Resultsmentioning
confidence: 99%
“…The electrodes were aligned to edges of the microchambers manually to keep their distance almost the same around the microchamber for uniform electrical stimulation of individual spheroids. Hybrids of hydrogel and organic electrodes are useful for biocompatible electronic systems and many types have been reported, however, the composite of PVA hydrogel and PEDOT‐coated CF (CF‐PEDOT) electrodes is reported for the first time as far as we know. The cover made of PVA hydrogel was tightly sealed to the body with pins.…”
Section: Resultsmentioning
confidence: 99%
“…e) Typical current–voltage curves of flexible organic transistors. Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International License ( http://creativecommons.org/licenses/by/4.0/) . Copyright 2016, Springer Nature.…”
Section: System Integrationmentioning
confidence: 99%
“…As the core of neurophysiologic monitoring, realizing high‐quality signal collection is an important topic in the research of neural electrode arrays. Related researches have indicated that stretchable/flexible neural electrode arrays, with their excellent mechanical and electrical performance, are superior candidates for the next generation of implantable devices 3, 4, 5, 6, 7, 8, 9, 10, 11. The successful development of stretchable/flexible neural electrode arrays hinges on good conformal contact between the array and the tissue, which enables excellent mechanical and electrical properties,3 as well as low‐cost, stable, and high‐throughput manufactural techniques.…”
Section: Introductionmentioning
confidence: 99%